Azwar Anas : teladan dari ranah Minang - Yusra, Abrar, 1943- (Jakarta : Penerbit Buku Kompas, 2011)
Biography of Azwar Anas, a cabinet officer during Suharto's administration.
Includes bibliographical references (p. 540-542) and index.
Keywords: Anas, Azwar; Cabinet officers -- Indonesia -- Biography; Indonesia -- Politics and government -- 1966-1998.